The challenges and uses of quantitative economic modeling of agricultural policy decision process in Africa: a case study of South African land redistribution - Olubode-Awosola, O. O.; Schalkwyk, H.D. van (2007)
The ineffectiveness of policy advice in most African countries could be attributed to problem of scientists not being able to present a holistic solution to policy problems. As a result, the consequences of policies are seldom indicated. It may be demanding to use a more comprehensive and quantitative research strategy in policy analysis because of limited ability to integrate the technical-biophysical with the economic, marketing and political aspects when analysing policy effects. There can be no doubt that such methods have important roles in illuminating policy effects thereby preventing policy mistakes. To exemplify this phenomenon, a forward-looking and prescriptive economic analysis that is being widely used in the developed world for agricultural policy analysis which supports the identification, prediction, prescription and comparison of alternative policy impacts was adopted to examine the potential effects of the South African land redistribution strategies on its agriculture with respect to equity and efficiency using an agricultural sector mathematical programming model. The results indicate that the current policy requires more economic imperatives, as it tends towards smallholder agriculture that cannot produce adequate yields to meet either domestic demand or a tradable volume. Given the challenges of a free market and the fact that the settled small-scale resource-poor (mainly black) farmers are less efficient compared to the large-scale (mainly white) farmers from whom government transfers land, the analysis allows to prescribe land redistribution strategies with policy recommendations that has more economic imperatives.